Total-body contrast-enhanced MRA on a short, wide-bore 1.5-T system: intra-individual comparison of Gd-BOPTA and Gd-DOTA. - Rasmus M; Bremerich J; Egelhof T; Huegli RW; Bongartz G; Bilecen D; Rasmus, M; Bremerich, J; Egelhof, T; Huegli, R W; Bongartz, G; Bilecen, D (European Radiology, 2008)
Total-body contrast-enhanced MRA (CE-MRA) provides information of the entire vascular system according to a one-stop-shop approach. Short, wide-bore scanners have not yet been used for total-body CE-MRA, probably due to their restricted field of view in the z-direction. The purpose of this feasibility study is to introduce an image protocol for total-body MRA on a short, wide-bore system. The protocol includes five to six table-moving steps and two injection runs. Two pharmacologically different contrast materials (CM) were applied in ten healthy volunteers in view of possible CM-dependent influences on the protocol outcome (Gd-Bopta, Gd-Dota). Differences consisted of significantly higher CNR with Gd-Bopta with a mean of 73.8+/-38.7 versus 69.1+/-34.3 (p=0.008), significantly better arterial visualization values with Gd-Dota with a mean of 1.26+/-0.44 versus 1.53+/-0.73 (p=0.003) and a tendency to less venous overlay with Gd-Dota, mean 1.19+/-0.44 and 1.34+/-0.72, respectively (p=0.065) (two-tailed Wilcoxon matched-pairs test). Overall 94% of the steps were valued as qualitatively excellent or good. The good results with both CM suggest a transfer to further patient evaluation.